2020
DOI: 10.1136/bmjopen-2019-033759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating spillover of HIV knowledge from study participants to their network members in a stepped-wedge behavioural intervention in Tanzania

Abstract: ObjectivesWe aim to describe the social network members of participants of a behavioural intervention, and examine how the effects of the intervention may spillover among network members.DesignSecondary analysis of a step-wedge randomised controlled trial.SettingChange agents (CAs) were recruited from waiting rooms of HIV treatment facilities in Dar es Salaam, Tanzania, and their network members (NMs) were recruited directly by CAs.ParticipantsWe enrolled 662 CAs in an HIV behavioural intervention. They, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…When one participant’s exposure affects another participant’s health outcome, the effect is broadly known as spillover (alternatively, interference or dissemination) [ 39 ]. Spillover has been well studied to improve vaccine delivery and effectiveness in a population [ 40 , 41 , 42 ]; however, there have been limited evaluations of spillover for HIV interventions [ 43 ]. Spillover can generally exist in a network when an intervention is delivered to individuals connected through disease transmission risk or some other mechanism [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…When one participant’s exposure affects another participant’s health outcome, the effect is broadly known as spillover (alternatively, interference or dissemination) [ 39 ]. Spillover has been well studied to improve vaccine delivery and effectiveness in a population [ 40 , 41 , 42 ]; however, there have been limited evaluations of spillover for HIV interventions [ 43 ]. Spillover can generally exist in a network when an intervention is delivered to individuals connected through disease transmission risk or some other mechanism [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Examples are trials to treat obstructive sleep apnoea, 7 chronic constipation, 8 malformations, 9 , 10 dementia, 11 to reduce household air pollution 12 and to evaluate self-management support programmes 13 and spillover of HIV knowledge. 14 The design of the individually randomized stepped-wedge design has not yet been thoroughly explored in the statistical literature. A recent study evaluated the efficiency of the individually randomized stepped-wedge design in trials with three time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Public health interventions in these populations often have disseminated effects, also known as indirect or spillover effects [9,10]. Recent work demonstrated that there are disseminated effects of HIV behavioral interventions, suggesting that intervening among highly-connected individuals may maximize spillover benefits to others [11]. Akin to other populations, PWID are embedded in social networks and communities (e.g., injection drug, non-injection drug, sexual risk network) in which they possibly exercise an influence upon other members [12,13].…”
Section: Introductionmentioning
confidence: 99%